Plan de desarrollo turístico en la Comunidad de Eugenio Espejo de Cajas, Parroquia de González Suárez, Cantón Otavalo - Conejo Terán, Tamia Saria (2015)
According to the World Tourism Organization, this contributes to economic growth, inclusive development and environmental sustainability, new trends are beginning to emerge in the world today, are mainly concentrated in the satisfaction of different, less massive and experiences better contact with rural societies. In Ecuador, the main economic activity is the exploitation of oil, followed by bananas, considered the backbone of the economy, contribute to economic growth, but in recent years, it is clear that tourism has become a development tool because our country is known for biodiversity that has each of its geographic regions are full of natural and cultural assets which include flora and fauna and some of them unique in the world having a great amplitude endemic species, the multiplicity of ethnic and indigenous nationalities that have managed to maintain their culture through the years, along with their partners thanks to the influence of the Cordillera of the Andes along the geographical size of the country we They provide a number of unique landscapes in the world. According to a statement by the Ministry of Tourism in October 2014 newsletter, he believes that tourism, had an increase of 14%. In the canton Otavalo, parish Suarez Gonzalez, Community of Eugenio Espejo of Cajas is; Due to its geographical location, has great tourism potential is not exploited locally, nationally and internationally. The participation of public, private and community institutions, in developing tourism, appropriate tourism could promote alternatives to improve the living conditions of its inhabitants, preserving the natural and cultural heritage supported projects, plans and programs.